2021
DOI: 10.1038/s41598-021-90545-4
|View full text |Cite
|
Sign up to set email alerts
|

Peganum harmala enhanced GLP-1 and restored insulin signaling to alleviate AlCl3-induced Alzheimer-like pathology model

Abstract: Peganum harmala (P. harmala) is a folk medicinal herb used in the Sinai Peninsula (Egypt) as a remedy for central disorders. The main constituents, harmine and harmaline, have displayed therapeutic efficacy against Alzheimer’s disease (AD); however, the P. harmala potential on sensitizing central insulin to combat AD remains to be clarified. An AD-like rat model was induced by aluminum chloride (AlCl3; 50 mg/kg/day for six consecutive weeks; i.p), whereas a methanolic standardized P. harmala seed extract (187.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 87 publications
1
15
0
Order By: Relevance
“…Twenty-two out of 32 studies tested naturally derived compounds, they include: compounds rich in flavonoids such as yuzu extract ( Yang et al, 2013 ), bee pollen extract ( Liao et al, 2019 ), N. incisum extract ( Jiang et al, 2020 ) and flavonoids of okra fruit ( Yan et al, 2021 ); compounds containing alkaloids, such as Puerariae radix ( Huang et al, 2019 ), ZiBuPiYin ( Ren et al, 2021 ), evodiamine ( Wang et al, 2018 ; Chou and Yang, 2021 ) and Peganum harmala ( Saleh et al, 2021 ); aquesous cinnamon extracts ( Madhavadas and Subramanian, 2017 ), which contain type A linked procyanidin trimer; schisandra chinensis extract ( Yan et al, 2017 ), which contains ligand diabenzo [a, c] cyclooctadiene; sea cucumber cerebrosides ( Li et al, 2019 ), which is a class of neural glycospinolipids; osthole ( Yao et al, 2019 ) which is a derivative of coumarin; curcumin ( SoukhakLari et al, 2018 ), which is the main ingredient of turmeric; litchi chinensis seed fraction ( Sun et al, 2020 ), which entails phenolic compounds and glycosides; Asiatic acid ( Ahmad Rather et al, 2019 ), which is a pentacyclic triterpenoid; Yonkenafil ( Zhu et al, 2019 ), which is a novel phosphodiesterase type 5 inhibitor and an analogue of sildenafil; 20(S)-protopanaxadiol, oleanolic acid ( Lin et al, 2021 ), which is an active compound found in ginseng and a Chinese herb gastrodin ( Wang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty-two out of 32 studies tested naturally derived compounds, they include: compounds rich in flavonoids such as yuzu extract ( Yang et al, 2013 ), bee pollen extract ( Liao et al, 2019 ), N. incisum extract ( Jiang et al, 2020 ) and flavonoids of okra fruit ( Yan et al, 2021 ); compounds containing alkaloids, such as Puerariae radix ( Huang et al, 2019 ), ZiBuPiYin ( Ren et al, 2021 ), evodiamine ( Wang et al, 2018 ; Chou and Yang, 2021 ) and Peganum harmala ( Saleh et al, 2021 ); aquesous cinnamon extracts ( Madhavadas and Subramanian, 2017 ), which contain type A linked procyanidin trimer; schisandra chinensis extract ( Yan et al, 2017 ), which contains ligand diabenzo [a, c] cyclooctadiene; sea cucumber cerebrosides ( Li et al, 2019 ), which is a class of neural glycospinolipids; osthole ( Yao et al, 2019 ) which is a derivative of coumarin; curcumin ( SoukhakLari et al, 2018 ), which is the main ingredient of turmeric; litchi chinensis seed fraction ( Sun et al, 2020 ), which entails phenolic compounds and glycosides; Asiatic acid ( Ahmad Rather et al, 2019 ), which is a pentacyclic triterpenoid; Yonkenafil ( Zhu et al, 2019 ), which is a novel phosphodiesterase type 5 inhibitor and an analogue of sildenafil; 20(S)-protopanaxadiol, oleanolic acid ( Lin et al, 2021 ), which is an active compound found in ginseng and a Chinese herb gastrodin ( Wang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies using natural compounds showed an overall positive effect ( Yang et al, 2013 ; SoukhakLari et al, 2018 ; Tang et al, 2018 ; Ahmad Rather et al, 2019 ; Huang et al, 2019 ; Li et al, 2019 ; Yao et al, 2019 ; Jiang et al, 2020 ; Chou and Yang, 2021 ; Ren et al, 2021 ; Saleh et al, 2021 ; Wang et al, 2021 ; Yan et al, 2021 ) on cognition, seven studies a moderately positive ( Madhavadas and Subramanian, 2017 ; Yan et al, 2017 ; Wang et al, 2018 ; Liao et al, 2019 ; Zhu et al, 2019 ; Sun et al, 2020 ; Lin et al, 2021 ) and one a negative effect ( Jiang et al, 2020 ). The effect of natural compounds on cognition were tested in dementia animal models in rat ( n = 7 out of 21 studies); mice ( n = 14 out of 21 studies), and in normal ageing animal model in mice [ n = 1 out of 1 study ( Jiang et al, 2020 )].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations